Recurrent Bacterial Meningitis in a Child with Mondini Dysplasia. (6th November 2014) - Kepenekli-Kadayifci, Eda; Karaaslan, Ayşe; Atıcı, Serkan; Binnetoğlu, Adem; Sarı, Murat; Soysal, Ahmet; Altınkanat, Gülşen; Bakır, Mustafa
Abstract : Mondini dysplasia, also known as Mondini malformation, is a developmental abnormality of the inner and middle ears that can cause hearing loss, cerebrospinal fluid (CSF) leakage, and recurrent bacterial meningitis (RBM), which is defined as two or more episodes of meningitis separated by a period of convalescence and the complete resolution of all signs and symptoms. An accurate diagnosis of the underlying pathology is crucial to prevent further episodes from occurring. Herein, we present a three-year-old boy with RBM and unilateral sensorineural hearing loss. During the evaluation to determine the etiology of the RBM, cystic malformation in the cochlea and vestibular dilatation consistent with Mondini dysplasia were detected via computerized tomography (CT) of the temporal bone.